An analysis on the impact of taxation and other regulatory requirements on corporate financial perfomance: the case of the Victoria Falls hotel partnership - Chiwona, Lesley Tafadzwa (Midlands State University, 2017)
Taxation and other regulatory requirements were cited by the management at TVFH as the major causes behind the sharp reduction of annual profits and unfavourable working capital between the periods 2013 to 2015.A descriptive research design was employed on a sample population of 22 staff members at TVFH most of whom were from the administrative departments. A total of 18 questionnaires were distributed to the sample population while interviews were carried out on 4 heads of departments who had unlimited access to information relevant to this research. The research found out that taxation and other regulatory requirements reduces organisational corporate profitability, reduces organisational working capital, compromises corporate growth , that tax planning does not significantly reduce organisational total costs, the only benefits of taxation and regulatory requirements were that money collected by government was being used for infrastructure development so as to attract more tourists and that local businesses enjoyed competitive advantage against foreign firms due to some selective laws introduced by government on foreign firms. The hotel’s management was recommended to participate in National Consultative Budgets preparation programmes so that they would air their views and explain to policy makers how they were affected by the regulatory framework, to engage in dialogues with the government or government agencies over their grievances, to do tax planning no how insignificant it is. The RBZ was also recommended to ensure that local banks provide a multi-processing facility for payments using international bank cards.